2022
DOI: 10.1021/acsami.2c05946
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film Morphology and Optical Properties of Photoisomerizable Donor–Acceptor Oligothiophenes

Abstract: It was recently reported that the most popular electron-accepting units introduced to π-conjugated oligomers studied for organic photovoltaic applications are susceptible to unwanted and even destructive photochemical reactions. The consequences of Z/E photoisomerization of the popular 2-(1,1dicyanomethylene)rhodanine (RCN) unit on the optical and morphological properties of a homologous series of RCNfunctionalized oligothiophenes are studied here. Oligomers consisting of one, two, or three thiophene units wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…We recently reported the ability of dicyanorhodanine (RCN) functionalized thiophenes to undergo Z / E configurational isomerization upon photoirradiation and observed that the solid-state morphologies and optoelectronic properties of thin films from RCN-containing oligomers can be significantly affected by configurational composition . Our structure–property studies could encourage opportunities for solar cell optimization through the consideration of this stereochemical feature.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We recently reported the ability of dicyanorhodanine (RCN) functionalized thiophenes to undergo Z / E configurational isomerization upon photoirradiation and observed that the solid-state morphologies and optoelectronic properties of thin films from RCN-containing oligomers can be significantly affected by configurational composition . Our structure–property studies could encourage opportunities for solar cell optimization through the consideration of this stereochemical feature.…”
Section: Introductionmentioning
confidence: 85%
“…It is well-appreciated that small changes in NFA structure can alter the morphology of the organic solar cell active layer and affect overall device efficiency . Common molecular-level approaches to optimizing OPV thin film morphology and charge transport include modifying the π-conjugated backbone structure and/or planarity and the structure and/or placement of solubilizing side chains. Modifications specific to INCN-containing molecules include altering the solubilizing alkyl chain placement along the π-conjugated backbone or on the indanone ring and introduction of halogen atoms or methoxy groups to various positions. The structural changes, while sometimes seemingly minor, can induce a higher film absorption coefficient, larger crystalline coherence, and higher electron mobility, ultimately leading to higher PCE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from mechanical features, intriguing designs for tuning the photophysical properties of the self-assemblies toward achieving intriguing applications are also important. Xue and co-workers synthesized oligomers consisting of one, two, or three thiophene units as pure Z isomers and with E isomer compositions of 25%, 53%, and 45%, respectively, for Z/E mixtures . The photophysical properties of solutions of Z isomers and Z/E mixtures were characterized, wherein changes to optical properties were evaluated on the basis of E isomer content.…”
mentioning
confidence: 99%
“…Xue and co-workers synthesized oligomers consisting of one, two, or three thiophene units as pure Z isomers and with E isomer compositions of 25%, 53%, and 45%, respectively, for Z/E mixtures. 12 The photophysical properties of solutions of Z isomers and Z/E mixtures were characterized, wherein changes to optical properties were evaluated on the basis of E isomer content. A novel supramolecular perovskite nanoassembly containing a Mn 2+alloyed (PEA) 2 PbBr 4 nanosheet (referred to as Mn:PbPeV NS) and [Cr(1,10-phenanthroline) 2 (5-nitro-1,10-phenanphroline)] 3+ (CrPS) was reported by Das et al toward oxidize biomolecules such as guanine and guanine-rich DNA by using light.…”
mentioning
confidence: 99%